A Comparison of the Characteristics of Planar and Axisymmetric Bluff-Body Combustors Operated under Stratified Inlet Mixture Conditions. (9th September 2013) - Paterakis, G.; Souflas, K.; Dogkas, E.; Koutmos, P.
Abstract : The work presents comparisons of the flame stabilization characteristics of axisymmetric disk and 2D slender bluff-body burner configurations, operating with inlet mixture stratification, under ultralean conditions. A double cavity propane air premixer formed along three concentric disks, supplied with a radial equivalence ratio gradient the afterbody disk recirculation, where the first flame configuration is stabilized. Planar fuel injection along the center plane of the leading face of a slender square cylinder against the approach cross-flow results in a stratified flame configuration stabilized alongside the wake formation region in the second setup. Measurements of velocities, temperatures, OH ∗ andCH ∗ chemiluminescence, local extinction criteria, and large-eddy simulations are employed to examine a range of ultralean and close to extinction flame conditions. The variations of the reacting front disposition within these diverse reacting wake topologies, the effect of the successive suppression of heat release on the near flame region characteristics, and the reemergence of large-scale vortical activity on approach to lean blowoff (LBO) are investigated. The cross-correlation of the performance of these two popular flame holders that are at the opposite ends of current applications might offer helpful insights into more effective control measures for expanding the operational margin of a wider range of stabilization configurations.